Maternal COVID-19 infection, clinical characteristics, pregnancy and neonatal outcome: a prospective cohort study at a tertiary care center in Central India - Tadas, Moushmi S. Parpillewar; S., Prashanthi; Tankhiwale, Mrunmayi; Singh, Monika (International Journal of Research in Medical Sciences, 2021)
Background: COVID-19 caused by severe acute respiratory syndrome coronavirus-2 is a global public health emergency as declared by WHO. Currently how it affects pregnancy very little is known. To identify maternal and neonatal risks associated with COVID-19 in pregnancy and to describe outcome a prospective cohort study was done. Associations were evaluated for all COVID-19 patients and for disease classified as mild versus moderate/severe disease. Methods: In this study COVID RT-PCR positive women who were admitted from 1 May to 31 August were included. Cases were classified according to their severity, investigations done and treated according to MOHFW (ministry of health and family welfare), India guidelines. Data was collected, analysed in terms of maternal and neonatal outcome. Results: Total 221 COVID-19 cases were admitted and 181 delivered during study period. There were 215 (97.28%) mild, 5 (2.71%) moderate and 1 (0.45%) severe cases. 210 (95.02%) were diagnosed in third trimester. Mean gestational age was 36.79±5.24 weeks and 3 out of 4 in moderate/severe category delivered preterm. 132 (59.73%) were asymptomatic. There was 1 ICU admission and 1 maternal death. Mean birth weight was 2.7±0.59 kg. There were 7 stillbirths, 14 NICU admission and 1 neonatal death. Conclusions: Majority of the covid infected women are asymptomatic are in mild category and there is no adverse maternal and neonatal outcome due to disease. Adversity of maternal and neonatal outcome depends on severity of disease and severity of disease is dependent on presence of co-morbidities.